Methods and Materials for Smart Manufacturing: Additive Manufacturing, Internet of Things, Flexible Sensors and Soft Robotics - Kumar, Arkadeep (Manufacturing letters, 2018)
With the advent of the Fourth Industrial Revolution, the realization of smart manufacturing and Industry 4.0, rapid advancements in technologies will change manufacturing of goods and services, apart from how we live. Innovation in digital technologies will have to be accompanied by advances in manufacturing processes and materials, to keep up with the transition. This paper will review and discuss the methods and material technologies present now, along with challenges to overcome, which will be critical for enabling smart manufacturing in the form of the Internet of Things (IoT), cyber-physical systems (CPS), human-robot interaction, augmented and virtual realities.